Testicular seminoma in a dog and its clinical, ultrasonographic, cytological and histopathological aspects: case report - Andrade, Amanda Bricio Pereira de; Vasconcelos, Juliana Gomes; Colares, Julia Carrah; Magalhães, Francisco Felipe de (Brazilian Journal of Case Reports, 2021)
Neoplasms are amongst the main death causes in dogs, with the testis as the second most affected tissue in non-neutered male dogs and seminoma as one of the most common type. In this study, a 12-years-old non-neutered male teckel dog was attended with no perceived clinic. The ultrasound examination revealed a hypoechogenic nodule of ellipsoid shape and slightly heterogeneous echotexture in right testis. The animal was referred for bilateral orchiectomy and histopathological evaluation confirmed the presence of diffuse seminoma in the right testicle and testicular degeneration in both testes. Prognostic factors evaluated in histopathology designated resolution with orchiectomy.